July protests shutdown (Cuba) - Voidly (Voidly Global Censorship Index, 2021)
CRITICAL severity censorship detected in Cuba. Data sourced from OONI.
Censorship Incident ID: CU-2021-0001. Severity: critical. Confidence: 90%